“The Role of Digital Storytelling in Enhancing Students’ Creative Thinking in School Clubs” - Djabbarova Nargiza Bakitovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the use of digital storytelling as a tool to enhance students’ creative thinking in school club activities. The study emphasizes how multimedia elements, interactive platforms, and collaborative projects can stimulate imagination, problem-solving skills, and innovation. Pedagogical strategies for effectively integrating digital storytelling into extracurricular programs are also discussed.